IMPACT OF FOLIAR APPLICATION OF SALICYLIC ACID ON SALINITY TOLERANCE IN SORGHUM - K , ANNY MRUDHULA (The Journal of Research ANGRAU, 2026)
Salinity is a major abiotic stress factor that restricts crop growth and yield, particularly inarid and semi arid regions. To mitigate the adverse effects of salinity on crop performance, a fieldexperiment was conducted during the kharif seasons of 2023 and 2024 at Kakarlamoodi village.The objective was to evaluate the influence of foliar application of salicylic acid on enhancingsalinity tolerance in sorghum. The study was arranged in a randomized block design with sixtreatments, replicated four times. Five concentrations of salicylic acid (50, 100, 150, 200, and 250mg L-1) along with a control were tested. Results indicated that foliar application of salicylic acid at250 mg L-1 produced significantly higher grain yields (6300 and 6235 kg ha-1), whereas the lowestyield was observed with 50 mg L-1. Furthermore, total chlorophyll content and antioxidant enzymeactivity were maximum under the 250 mg L-1 treatment, highlighting its effectiveness in improvingsorghum performance under saline conditions.